Detecting the corruption pattern and measuring the corruption detection pace at the Indonesian village level - Prihatmanto, Hepnu Nur; Munajat, Mas Dadang Enjat; Irawati, Ira (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
Despite widespread reports of corruption in 74,961 village authorities in Indonesia, the government has yet to establish an effective mechanism to detect and prevent corruption at the village government level. Therefore, this study provides an overview of corruption in villages by perpetrator profile, village development, and corruption detection pace to identify the highest-risk authorities exposed to corruption and implement preventive measures. Supported by a qualitative descriptive strategy for interpreting the data, this study analyzed 186 villages whose governing bodies engaged in corruption and were prosecuted by law enforcement officials from 2015 to 2021. The result shows that Java is more focused than other regions on prosecuting corruption cases in rural areas. Moreover, corruption cases in Java and Sumatra regions concentrate on developing villages. Outside of these two regions, most corruption occurs in disadvantaged villages. Village corruption cases were detected on average 2.72 years after the onset of corruption. These findings address a gap in previous research by exploring the variation in losses resulting from village corruption cases across different regions. The study underscores the significance of implementing regulations that mandate regular audits and other detection policies customized to specific attributes, such as region, development level, perpetrator profiles, and fraudulent scheme trends.